A Web-Based Wound Information and Recovery Prediction System - Ting, Chris Lik Yong (Universiti Malaysia Sarawak (UNIMAS), 2020)
Injuries are happening all the time and wounds are shaped in the process. Untreated or uncared wound can lead to a more serious conditions which may require more time for the wound to be recovered. It is important to take care of the wound before it is getting more serious. Visiting to a hospital is difficult for some people as it is time-consuming. Things may get worse when a hospital is filled up with a lot of patients almost every day and the lack of medical personnel and facilities in the hospital reduces the efficiency of the wound assessment and documentation process. There is no wound care management for the hospital where all the wound assessments are documented using paperwork. For these purposes, a web application is developed to document all the wound assessments for better wound care management. The web application allows the doctors or patients to access and document the wound assessments whenever and wherever using any platform that can access the web. All the important aspects for the wound recovery such as location, size and photo of the wound, existing or previous medical problem, age and gender, BMI and support from family members are documented to provide a constructive view to the doctors and patients for decision-making. The doctors can communicate easily with the patients and vice versa using the proposed system. The system also provides wound recovery prediction using machine learning algorithms. This system is aimed to provide a more effective and efficient wound care management.